2012
DOI: 10.1007/s00249-012-0861-1
|View full text |Cite
|
Sign up to set email alerts
|

Multiple actin binding domains of Ena/VASP proteins determine actin network stiffening

Abstract: Vasodilator-stimulated phosphoprotein (Ena/VASP) is an actin binding protein, important for actin dynamics in motile cells and developing organisms. Though VASP's main activity is the promotion of barbed end growth, it has an F-actin binding site and can form tetramers, and so could additionally play a role in actin crosslinking and bundling in the cell. To test this activity, we performed rheology of reconstituted actin networks in the presence of wild-type VASP or mutants lacking the ability to tetramerize o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 50 publications
0
20
0
Order By: Relevance
“…Indeed, Ena/VASP is found to magnify the effect of fascin on network rigidity, perhaps explaining the presence of these two proteins in filopodia (301). However, on their own, Ena/VASP proteins only very modestly increase the rigidity of actin networks, possibly due to the flexibility the Ena/VASP tetramer (101,302).…”
Section: E Parallel Actin Bundlesmentioning
confidence: 99%
“…Indeed, Ena/VASP is found to magnify the effect of fascin on network rigidity, perhaps explaining the presence of these two proteins in filopodia (301). However, on their own, Ena/VASP proteins only very modestly increase the rigidity of actin networks, possibly due to the flexibility the Ena/VASP tetramer (101,302).…”
Section: E Parallel Actin Bundlesmentioning
confidence: 99%
“…Fluorescently labelled actin was purified from skeletal rabbit muscle and labelled with Alexa Fluor-488 or -594 (Invitrogen) 70 . Recombinant GSTtagged mouse Fascin (the plasmid was a gift from S. Hansen and R. D. Mullins, University of California San Francisco, USA) was produced in E. coli and purified using standard procedures.…”
Section: Sample Preparation For Tirf Microscopy Of In Vitro Reconstitmentioning
confidence: 99%
“…However, interestingly, Cyto B strongly suppressed these phosphorylation events, indicating that actin cytoskeleton disruption itself or actin cytoskeleton disruption-linked molecular events may autologously participate in regulating upstream events for actin polymerization. Indeed, it has been reported that VASP and HSP27 are actin-binding proteins (Wang and Bitar, 1998; Gentry et al ., 2012). Thus, the EVH2 domain is known as an important part of VASP for actin binding capacity (Gentry et al ., 2012), indicating direct regulation between actin cytoskeleton and the activation of VASP and HSP27.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, it has been reported that VASP and HSP27 are actin-binding proteins (Wang and Bitar, 1998; Gentry et al ., 2012). Thus, the EVH2 domain is known as an important part of VASP for actin binding capacity (Gentry et al ., 2012), indicating direct regulation between actin cytoskeleton and the activation of VASP and HSP27. Mean-while, considering that Src is a critical enzyme linked to actin cytoskeleton (Kim et al ., 2010), a possibility that actin cytoskeleton-controlled Src is able to modulate the phosphorylation of VASP and HSP27 could be hypothesed.…”
Section: Resultsmentioning
confidence: 99%